Study of Subtitling Strategy in The School for Good and Evil: Kajian Strategi Penerjemahan dalam Subtitle Film The School for Good and Evil - Pramadanti, Muthia; Aryanika, Septa (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This research aims to analyze what subtitling strategy are used in The School for Good and Evil based on Gottlieb's theory and the accuracy of translation in The School for Good and Evil based on Larson's theory. This research uses descriptive qualitative method to analyze the data. The data source used is the English-Indonesian script of the movie The School for Good and Evil. The result of this research is 6 out of 10 strategies used with 588 data including expansion with 12 data, paraphrase with 89 data, transfer with 421 data, imitation with 24 data, condensation with 38 data, and deletion with 4 data. Which is not found transcription, dislocation, decimation, and resignation. The accuracy of the translation with 588 data was found to be accurate, which means that the translation in the movie The School for Good and Evil is accurate. This research focuses on translation strategies and translation accuracy in The School for Good and Evil movie aired on Netflix. This study can be an additional information for researchers who take the same research